Experiences of Families Separated across Borders Following Modern Slavery and Human Trafficking - Treadaway, Rebecca (Anti-Trafficking Review, 2025)
Within the United Kingdom’s system for identifying survivors of modern slavery and human trafficking, survivors coming from overseas account for nearly 75%. This data indicates that many survivors are separated from family in the process of trafficking, yet little is known about the impact this separation has on them and their families. This article addresses this gap by analysing case data and twelve interviews with anti-slavery practitioners. The findings demonstrate that separation from family can hamper survivors’ recovery, due to the distress caused by the separation and an ongoing need for survivors to provide for family overseas. The process of family reunification is unnecessarily lengthy and complex, and survivors receive limited support for this aspect of recovery. The impact of separation on families is significant, and a ‘family-oriented’ approach to survivor support should be developed alongside measures to address the structural issues that create extended periods of separation and precarity for migrants.